Protective effect of resveratrol against hydrogen peroxide-induced oxidative stress in bovine skeletal muscle cells. (March 2022) - Zhang, Xianglun; Liu, Xiaomu; Wan, Fachun; You, Wei; Tan, Xiuwen; Sheng, Qingkai; Li, Chuanhao; Hu, Zhuran; Liu, Guifen; Zhao, Hongbo
Abstract: The objective of this study was to investigate the protective effects and the underlying mechanisms of resveratrol (RES) against hydrogen peroxide (H2 O2 )-induced oxidative stress in bovine skeletal muscle cells (BMCs). Pretreatment of BMCs with RES prior to H2 O2 exposure increased cell viability, attenuated reactive oxygen species, and stabilized the redox state. H2 O2 exposure activated sirtuin type 1 (SIRT1) and nuclear factor E2-related factor 2 (NRF2)-mediated signaling pathways. Pretreatment with RES did not alter SIRT1-regulated genes but inhibited the upregulation of NRF2, whereas enhanced heme oxygenase 1 (HO-1) expression. Pretreatment with RES prior to H2 O2 exposure failed to suppress NRF2 expression when NRF2 was knocked down by RNA interference. However, HO-1 expression still could be induced by RES. These results suggest that RES has benifical effects against oxidative stress. NRF2-mediated pathway play an important role, and HO-1 upregulation is the key process in RES regulation. RES may be used as a therapeutic agent for meat quality improvement in beef cattle.